2015
DOI: 10.1111/ecin.12299
|View full text |Cite
|
Sign up to set email alerts
|

Using the Pareto Distribution to Improve Estimates of Topcoded Earnings

Abstract: Inconsistent censoring in the public‐use March Current Population Survey (CPS) limits its usefulness in measuring labor earnings trends, as previous approaches for imputing topcoded earnings systematically understate top earnings. Using Pareto estimation methods with less‐censored internal data, we create an enhanced cell‐mean series to capture top earnings in the public‐use data. Annual earnings inequality trends since 1963 using our series largely mirror those found by Kopczuk, Saez, and Song using social se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…15,19 If the participant was in the highest bracket at each visit, we multiplied the value of the highest income category by 1.5 following the Pareto distribution. 20 Thus, the highest income bracket at both visits was interpreted as $75 000.…”
Section: Key Pointsmentioning
confidence: 99%
“…15,19 If the participant was in the highest bracket at each visit, we multiplied the value of the highest income category by 1.5 following the Pareto distribution. 20 Thus, the highest income bracket at both visits was interpreted as $75 000.…”
Section: Key Pointsmentioning
confidence: 99%
“…Freenenberg and Poterba (1993) have shown that this interpolation provides good empirical estimates of the incomes of the top fractals. Subsequent studies of income distribution at the top have in fact confirmed the reliability of the Pareto interpolation, including among others Piketty and Saez (2003), Atkinson and Piketty (2007) and Atkinson, Piketty and Saez (2011) and recently Armour et al(2014).…”
Section: Income Interpolationmentioning
confidence: 79%
“…We again find that the topmost observations may be distributed too narrowly compared to what would be expected under the Pareto law (table A5). Armour et al (2016) apply a similar method using known information on the number of top-coded observations; our method is not limited to the case of topcoding, but also allows for general mismeasurement, outliers, or nonresponse. Jenkins (2017) discusses the appropriate type of Pareto specification and cutoffs for estimation.…”
Section: Available Datamentioning
confidence: 99%
“…To compare the actual distributions of top expenditures to distributions that may be predicted in the given countries, and study the presence of extreme values in our data, we follow an approach applied by Atkinson, Cowell, Jenkins, Piketty and others to summarize the dispersion of economic outcomes by a parametric distribution, report properties of the estimated distribution, and use the estimates to correct the observed top tail for suspected statistical problems (Atkinson et al 2011;Armour et al 2016). 5 9Inequality estimates imputed from parametric distributions can be less sensitive to extreme observations and sampling variations than non-parametric observations from actual survey data.…”
Section: Replacement Using Values From a Pareto Distributionmentioning
confidence: 99%